O papel do diretor escolar: uma discussão colaborativa - Aranha, Elvira Maria Godinho (2009)
This dissertation aims to investigate the overall production process of shared meanings related to school administration, starting from the collaborative process developed between a researcher and the director of a municipal public school. More specifically, the aim of this research work is to elicit how the relationship between researcher and director allowed for the process, having its focus on building a more democratic and participatory school. Developed in a municipal school of Children Education in the City of São Paulo, this work is based on the methodology of Collaborative Critical Research - PCCol (MAGALHÃES, 1994/2007, 1998/2007, 2009p). Considering this kind of research suggests there should be learning and development for all involved, the theoretical frame of the study is based on the Socio-Cultural-Historical Activity Theory (TASCH), and taken into account are the discussions of Vygotsky, (1927/2004, 1934/2001, 1925-1930/2004, 1925/2004, 1930/2004, 1926/2004), Leontiev (1977, 1978, 1983, 2004), Daniels (1994, 2001, 2002), Newman & Holzman (1993/2002) and Engeström (1987, 1999 a, 1999b,1999c 7) on learning and development, awareness and mediation. It is also supported by the studies of Bakhtin´s Circle (1929-1930/2006, 1934-35/1998). The Activity focused in this study has been defined as director training. The analysis and discussion of results was based on clippings of selected interactions between the researcher and the director over nine meetings and guided by categories based on the texts of Bronckart (1999/2007), Kerbrat-Orecchioni (2006), Pontecorvo (2005), Wertsch & Smolka (1993/1999) Brookfield & Preskill (2005). The results mentioned here show that: (i) the relationships developed between the participants enabled learning and development, (ii) the original meanings were re-signified and (iii) the interactions developed had an impact on the director´s action planning and suggested changes in the immediate context. They also point to the importance of building mediation devices which represented both the sharing of meanings and the opportunity to advance in what concerns the Director Training process Activity